More on Growth and the Balance of Payments: The Adjustment Process - Douglas D. Purvis (Queen's University, Department of Economics, 1972)
The effect of an economy's growth on its balance of payments has been a subject which has received a good deal of attention in the recent literature in international economics. Much of this attention derives from general dissatisfaction with the theoretical and empirical aspects of the standard Keynesian analysis which argues that, via the existence of a positive marginal propensity to import, growth in a country's income will lead to an increase in imports. Hence, the argument proceeds, for given exports, growth leads to a deterioration in the balance of payments. As a result, we have developed the "monetary approach" to growth and the balance of payments emphasizing the role of asset market equilibrium. Further we have demonstrated this approach to be capable of yielding insights into the short-run or transitional effects on the balance of payments of various exogenous disturbances. It is hoped that the examples provided in the following article will highlight the importance of considering impact effects and adjustment processes when looking at balance of payments or any other macroeconomic phenomena, and that future research will reflect such considerations.
Keywords: 330